2011
DOI: 10.2514/1.b34067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tip Clearance on the Performance of a Three-Bladed Axial Inducer

Abstract: This paper illustrates the results of an experimental campaign conducted in the Cavitating Pump Rotordynamic Test Facility. Tests have been carried out at two values of the blade tip clearance on the three-bladed DAPAMITO3 inducer, designed by means of a reduced-order model, with geometry and noncavitating performance representative of typical space rocket inducers. Different cavitating behaviors have been observed at different values of the blade tip clearance, particularly near breakdown conditions. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…To use the high-performance region effectively, it is necessary to allow controllable cavitation to occur at the inducer. A considerable number of studies has been conducted to investigate this effect, but they have mainly focused on water cavitation [1][2][3].…”
mentioning
confidence: 99%
“…To use the high-performance region effectively, it is necessary to allow controllable cavitation to occur at the inducer. A considerable number of studies has been conducted to investigate this effect, but they have mainly focused on water cavitation [1][2][3].…”
mentioning
confidence: 99%
“…It was found that for the inducer with a smaller inlet blade angle and a larger sweep, RC at the design and larger flow coefficients was avoided. Torre, et al (2011) experimentally illustrated the influence of the tip clearance on RC on a threebladed axial inducer. It was observed that the maximum amplitude of the pressure oscillation at the frequency of RC decreases with an increasing tip clearance.…”
Section: Introductionmentioning
confidence: 99%
“…8 Tabar and Poursharifi 9 have studied the cavitation inception in an axial flow pump and figured out that the tip sharpness and geometry are the most important parameters that affect the cavitation area. Torre et al 10 have also figured out that different tip clearances can lead to different cavitating behaviours. The mixed-flow pump has geometric similarities with axial flow pumps and inducers especially at impeller region, so the tip clearance should also be concerned and studied.…”
Section: Introductionmentioning
confidence: 99%